Adoption and Use of Social Media in Manufacturing Firms – Some Evidence from Kasapreko Company Limited and Guinness Ghana Breweries Limited - Amponsah-Twumasi, Y. (University Of Ghana, 2016)
Social media provides a virtual network place where individual and organisations are able to enjoy and express their opinions, exchange opinions, distribute and control messages anywhere anytime. The use of SM has aided an exceptional growth in the way people interact with each other and do business. Unlike the traditional advertising tools of marketing communications, SM platforms, allow consumers to make inputs into the brand messages displayed by various companies, making SM a more reliable source of information. The main aim of this study was to assess the promotional strategies that Kasapreko Company Limited and Guinness Ghana Breweries Limited adopt for harnessing user-generated content on their digital platforms. Data was collected using an interview guide, two representatives from Kasapreko Company Limited and Guinness Ghana Breweries Limited were interviewed face-to-face, and their responses audio recorded. The responses were manually transcribe, coded and put into themes. Facebook pages of the two industries were visited and specific promotional messages extracted. The study revealed that, organisations use promotions and sponsorships as a way of attracting both individual and other organisations to their SM platforms. Although the organisations sees SM as a means of reaching their customers in the shortest possible time and helping customers to become aware of existing and new products, yet both organisation were not able to specifically quantify the revenue generated so far as the use of SM is concern. The study concluded that, although the real benefits derived from social media could not be quantified by the organisations, it is still worth staying on the digital platforms. The study recommended that, management of the study organisations find ways to strategically quantify the real benefits derive from social media to justify their continual presence.
Thesis (MPhil.)
Keywords: Social Media; Manufacturing Firms; Breweries; Traditional Advertising; Ghana